Adaptive damper control for HVAC systems based on human occupancy and indoor parameters: A development study - Vasanthkumar, C. H.; Roselyn, J. Preetha; Uthra, R. Annie; Devaraj, D. (Frontiers in Energy Research, 2022)
Occupancy based strategies for the control of ventilation systems in the buildings are effective for achieving the energy savings and user comfortness. More than 50% savings in energy consumption can be achieved by control of Heat, Ventilation and Air Conditioning (HVAC) system with accurate sensory and occupancy information. In this paper, the flow control through the damper of Variable Area Valve (VAV) system and the speed of the blower VFD drive in the HVAC system are controlled based on human occupancy and indoor parameters namely temperature and humidity, segment wise in the building. The flapper angle of the VAV is estimated in the proposed model using the indoor temperature, external temperature and the number of occupants. The occupancy data is fed to the proposed controller to control the flow through ducts of HVAC systems flapper angle of VAV to maintain the human comfort. Based on the proposed occupancy scheme it is possible to detect the abnormalities in the energy utilization and to trace out maximum utilization in the building area based on this the control parameters of the HVAC are adjusted for comfortable indoor environment. To evaluate the performance of the VAV system with the proposed control strategy temperature and flow distribution is simulated through Fluent software. A laboratory grade prototype was developed incorporating the proposed control strategy and tested under three different conditions and the results are reported, the experimental results show that an energy saving of 18% can be achieved.